Проектирование и расчет пластинчатых теплообменников с разной конфигурацией профиля каналов - Бабак, Татьяна Геннадиевна; Хавин, Геннадий Львович (Национальный технический университет "Харьковский политехнический институт", 2018)
У багатьох застосуваннях хімічної технології, зокрема в нафтохімічній промисловості, за умовами рекуперації енергії є значна різниця між витратами гарячого і холодного теплоносіїв. У цьому випадку має місце різке зниження швидкості теплоносія в каналах з меншою витратою, що призводить до падіння величини коефіцієнта тепловіддачі з боку цього теплоносія і загального коефіцієнта теплопередачі апарата. Такий ефект сприяє падінню величини дотичного напруження на стінці і, як наслідок, до інтенсифікації забруднення поверхні теплообміну і порушення екологічної безпеки в процесі експлуатації. Представлені переваги і запропоновано спосіб інтенсифікації процесу теплопередачі в каналах розбірних та зварних пластинчатих теплообмінників з круглою пластиною за рахунок використання каналів з різною конфігурацією профілю по стороні теплоносіїв, що нагріває і що нагрівається. Використання такої конструкції призводить до вирівнювання швидкостей потоків в каналах, зменшення їх кількості і збільшенню величини дотичного напруження на поверхні теплопередачі пластин. Досліджується вплив геометричних параметрів гофрування на її здатність до теплопередачі. Для реалізації проектування зварних пластинчастих теплообмінників з каналами різного поперечного перерізу (різної висоти і кроку гофрування) було розроблено математичне забезпечення, що реалізує можливість такого моделювання. Загальна ідея алгоритму розрахунку полягає в знаходженні оптимального значення довжини пластини, яка визначає її площа, і кількості пластин за умови задоволення всім необхідним умовам по передачі тепла і гідравлічним втратам в апараті. Довжина пластини є функцією гофрування пластини і, відповідно, визначає швидкість теплоносіїв в каналах і їх здатність до теплопередачі. Розглянуто конкретне застосування з розрахунку теплообмінників з каналами з різною висотою гофрування. Аналіз отриманих результатів дозволив зробити висновок про те, що при фіксованій висоті гофри по стороні одного з теплоносіїв (з меншою витратою), зміна загального розміру площі поверхні теплопередачі носить екстремальний характер.

In many applications of chemical technology, in particular in the petrochemical industry, under the conditions of energy recovery there is a significant difference between the consumption of hot and cold heat carriers. In this case, there is a very strong decrease in the velocity of the heat carrier in the channels with less flow, which leads to a drop in the coefficient of heat transfer from this heat carrier and the overall heat transfer coefficient of the unit. Such an effect contributes to the drop in the magnitude of the tangential stress on the wall and, as a consequence, to the intensification of the heat transfer surface fouling and the violation of environmental safety during operation. Advantages are presented and a method for intensifying the process of heat transfer in the channels of gasketed and welded plate heat exchangers with a circular plate is proposed. It realized due to the use of channels with different profile configurations along the side of heating and heated carriers. The use of such a design leads to equalization of the flow rates in the channels, a reduction in their numbers and an increase in the shear stress on the heat transfer surface of the plates. The influence of the geometric parameters of the corrugation on its heat transfer capacity is investigated. To implement the design of welded plate heat exchangers with channels of different cross-section (different height and corrugation step), a software was developed that implements the possibility of such a modeling. The general idea of the calculation algorithm is to find the optimal value of the length of the plate, which determines its area, and the number of plates provided all the necessary conditions for the heat transfer and hydraulic pressure drops in the device are met. The length of the plate is a function of the plate corrugation and, accordingly, determines the velocity of the heat carrier in the channels and their ability to heat transfer. A specific application for the calculation of heat exchangers with channels with different heights of the corrugation was considered. The analysis of the obtained results allowed concluding that with a fixed height of the corrugations on the side of one of the heat transfer carrier (with less consumption), the change in the total value of the heat transfer surface area has extreme character.
Design and calculation of plate exchangers with different configuration of channel profile
Keywords: высота гофрировки; анализ теплопередачи; сопротивление загрязнению; потери давления; температура; давление